Conversion of glucose to methyl glycolate in subcritical methanol. Issue 29 (22nd March 2023) - Weng, Yujing; Zou, Min; Liu, Xuying; Gu, Junchao; Liu, Zhijie; Fan, Yunchang; Zhang, Yulong; Liao, Yuhe
Abstract : Sub-supercritical methanol and the phenol/quinone redox system were combined to promote the conversion of glucose to methyl glycolate. Abstract : Methyl glycolate (MG) is an important biodegradable PGA plastic monomer. Herein, a green approach to synthesize MG by methanolysis of glucose is proposed, in which the subcritical methanol and phenol/quinone redox system were combined to promote the reversible C–C cleavage and oxidation during the cascade reaction of glucose to MG.